Adaptation and Validation of The Children’s Worlds Subjective Well-Being Scale (CW-SWBS) in Indonesia - Ihsana Sabriani Borualogo; Ferran Casas (Jurnal Psikologi, 2019)
The Indonesian research team participating in the Children’s Worlds international project has used a new context-free multi-item scale named CW-SWBS (Children’s Worlds Subjective Well-Being Scale). This psychometric instrument was previously never used in Indonesia. This study aimed to validate the adapted Indonesia language version for a representative sample of children who are elementary students in West Java province (N = 22,616), ranging from 8, 10, to 12-year-olds. Confirmatory Factor Analysis (CFA) was used to test the fit of the psychometric scale, and multi-group CFA was used to check the comparability between answers given by gender and school types. Result findings showed that the instrument displays excellent fit for measuring life satisfaction in Indonesian children using five items, instead of the six original items. Answers to the items of the CW-SWBS by gender and school types were demonstrated to be comparable, suggesting that there was no different answering style between individuals in these studied groups.